2014
DOI: 10.5455/aim.2014.22.379-384
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Internet Training on Posture Reform of Computer Users in Iran

Abstract: Background and Purpose:Musculoskeletal disorders are of common problems among computer (PC) users. Training of posture reform plays a significant role in the prevention of the emergence, progression and complications of these diseases. The present research was performed to study the effect of the Internet training on the posture reform of the Internet users working in two Iranian universities including Sistan and Baluchestan University and Islamic Azad University of Zahedan in 2014.Materials and Method:This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The results showed that the largest number of participants were in the age groups 30–40 and 20–30 years old, and the number of old participants was low, which could be due to lack of literacy, lack of mobile and internet facilities, and unwillingness to complete the questionnaire electronically. Studies have shown that the majority of internet users in Iran and worldwide comprise younger age groups (Keykhaie et al 2014 ; Langarizadeh et al 2018 ; Salehi et al 2014 ). This was in line with similar studies (Abdelhafiz et al 2020 ; Gu et al 2015 ; Zhong et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the largest number of participants were in the age groups 30–40 and 20–30 years old, and the number of old participants was low, which could be due to lack of literacy, lack of mobile and internet facilities, and unwillingness to complete the questionnaire electronically. Studies have shown that the majority of internet users in Iran and worldwide comprise younger age groups (Keykhaie et al 2014 ; Langarizadeh et al 2018 ; Salehi et al 2014 ). This was in line with similar studies (Abdelhafiz et al 2020 ; Gu et al 2015 ; Zhong et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Improved education and training regarding internet and computer use has significant impact on posture care in computer users. [ 10 ] Replacing a sedentary life with activities involving good physical activities and proper diet plays an important part in reducing these problems. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…3 (38)(39)(40) 8 (10,27,(40)(41)(43)(44)(45)(46) 1 (43) 1 (43) Theme 4 1 (50) Theme 5 2 (30,56) 3 (35,51,52) 1 (57) 1 (53) 1 (55) Theme 6 2 (79,90) 17 (62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78) 9 (58)(59)(60)(61)(91)(92)(93)(94)(95) Theme 7…”
Section: Retrieved Articlementioning
confidence: 99%
“…An analysis of online cancer related news revealed that only 7 % of the news sources reported using the results from randomized controlled trials published in peer-reviewed journals [55]. Internet-based training interventions have been shown to improve posture among computer users [56]. Such alternative ergonomic-based treatments may help prevent emergence, progression, and complications of musculoskeletal disorders.…”
Section: Theme 5: Need For Cam Informationmentioning
confidence: 99%